Korelasi Kadar Hormon Serotonin dengan Level Kualitas Hidup: Psikososial Wanita Menopouse - Wiwik Agustina; Widiya Fauziah Aszhari (Lontara Journal of Health Science and Technology, 2026)
In 2020, the number of women who had entered menopause reached 30,3 million people, equivalent to 15,3% of Indonesia's total population. In the menopause phase, there are quality of life changes in women, including changes in hormone function, especially in the serotonin hormone. This study aims to determine the correlation between serotonin hormone levels and the level of quality of life: psychosocial of menopausal women. This study uses a correlational design with cross-sectional data collection. The population of all menopausal women was 105, aged 45-65 years in the Pakis and Polowijen Districts of Malang City, with a sample of 83 taken using purposive sampling with the criteria of having entered menopause less than 5 years ago, having a husband, and not having had a uterus removed. The data collection instrument used MENQOL (Menopause Quality of Life) and ELISA techniques. The results of this study stated that there was a significant correlation between serotonin values ​​and the level of quality of life:psychosocial of menopausal women (spearman rho correlation; ρ value = 0.000; r = 0.734), with details of more than half of respondents (52%) have a good quality of life: psychosocial and the majority of respondents (63%) who had low serotonin values. These results indicate that serotonin values ​​correlate significantly with the level of quality of life:psychosocial in menopausal women. As serotonin levels decrease, the quality of life:psychosocial also decreases, thus changes in quality of life: psychosocial can be reduced by carrying out certain activities and maintaining good and positive social and family relationships.